ylm Has More than a (Z Anchor) Ring to It! - White, Maria L. (J Bacteriol, 2021)
The division and cell wall (dcw) cluster is a highly conserved region of the bacterial genome consisting of genes that encode several cell division and cell wall synthesis factors, including the central division protein FtsZ. The region immediately downstream of ftsZ encodes the ylm genes and is conserved across diverse lineages of Gram-positive bacteria and Cyanobacteria. In some organisms, this region remains part of the dcw cluster, but in others, it appears as an independent operon. A well-studied protein coded from this region is the positive FtsZ regulator SepF (YlmF), which anchors FtsZ to the membrane. Recent developments have shed light on the importance of SepF in a range of species. Additionally, new studies are highlighting the importance of the other conserved genes in this neighborhood. In this minireview, we aim to bring together the current research linking the ylm region to cell division and highlight further questions surrounding these conserved genes.